2013
DOI: 10.1210/en.2012-1602
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Regulation of Gonadotropin-Releasing Hormone Neuron Excitability in Male and Female Mice

Abstract: Numerous in vivo studies have shown that dopamine is involved in the regulation of LH secretion in mammals. However, the mechanisms through which this occurs are not known. In this study, we used green fluorescent protein-tagged GnRH neurons to examine whether and how dopamine may modulate the activity of adult GnRH neurons in the mouse. Bath-applied dopamine (10-80 M) potently inhibited the firing of approximately 50% of GnRH neurons. This resulted from direct postsynaptic inhibitory actions through D1-like, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 31 publications
2
54
1
3
Order By: Relevance
“…GABA co-expression patterns appeared similar across both dorsal and ventral populations, suggesting similar co-expression proportions for both TIDA and A12 neurons. Dopamine has been shown to have potent inhibitory effects on GnRH neuron excitability [53] , and there is substantial ultrastructural evidence for dopamine synaptic inputs to GnRH neurons [54][55][56] ; however, it is questionable whether this input arises from the ARN [57] . Interestingly, the present study found that TH-positive neurons in males were more likely to be GABAergic than in females, a sex difference that has not been previously reported in the ARN.…”
Section: Discussionmentioning
confidence: 99%
“…GABA co-expression patterns appeared similar across both dorsal and ventral populations, suggesting similar co-expression proportions for both TIDA and A12 neurons. Dopamine has been shown to have potent inhibitory effects on GnRH neuron excitability [53] , and there is substantial ultrastructural evidence for dopamine synaptic inputs to GnRH neurons [54][55][56] ; however, it is questionable whether this input arises from the ARN [57] . Interestingly, the present study found that TH-positive neurons in males were more likely to be GABAergic than in females, a sex difference that has not been previously reported in the ARN.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results strongly suggest that dopaminergic inhibition of GnRH1 neurons is achieved via D2R-mediated opening of potassium channels. Similarly, dopamine regulates hypothalamic GnRH neurons in mice via both D1Rs and D2Rs, the latter also via potassium channels (Liu and Herbison, 2013). The identity of the potassium channel involved in D2R-mediated inhibition of mammalian and fish GnRH neurons is unknown, although candidates include G-protein-coupled inwardly rectifying and ATP-sensitive channels.…”
Section: D2r Agonists Directly Inhibit Gnrh1 Neuronsmentioning
confidence: 99%
“…Dopamine has been shown to be one of the most potent inhibitors of GnRH neuronal excitation (29). To determine when kisspeptin neurons in the AVPV start to pro- Blue arrowheads indicate estrogen-sensitive kisspeptin neurons that are not synaptically connected to GnRH neurons.…”
Section: Increase In Dopaminergic Avpv Kisspeptin Neurons During Pubertymentioning
confidence: 99%